A Statistical Assessment of Drinking Water Quality: A Case Study of Doburca Treatment Plant, Bursa - Yılmaz, Damla; Aras, Egemen; Vaheddoost, Babak (Fırat University, 2024)
In order to provide and maintain urban health standards, assessing the quality of drinking water is an essential step. As a result of different pollutant factors (climate, heavy metals, vegetation, human activities, etc.), it is inevitable that the quality of water resources decreases day by day. In this study, the data of 21 water samples taken between January 2021 and June 2021 from the water drinking facility providing drinking water to Bursa were examined. Firstly, the strength and direction of the relationship between 10 different parameters (electrical conductivity (EC), copper (Cu), nickel (Ni), nitrate (?NO?_3^-), arsenic (As), iron (Fe), total dissolved substances (TDS), total alkalinity (TA), total hardness (TH) and dissolved oxygen (DO)) were evaluated with the help of relation analysis, water quality index, and polynomial curve fitting. The relationship of the parameters that do not have a linear correlation was also interpreted and finally, as a result of using the weighted arithmetic water quality index (WAWQI), it was determined that the potability of the water quality in the allocated water reservoir was at the 'excellent' level and fulfills the requirements.

Kentsel sağlık standartlarını sağlamak ve bu standartları sürdürebilmek için içme sularının kalitesini değerlendirmek öncelikli adımdır. Farklı kirletici faktörlerin (iklim, ağır metaller, bitki örtüsü, beşeri faaliyetler vs.) su kaynaklarını tehdit etmesi neticesinde günden güne kalitenin düşmesi kaçınılmaz olmaktadır. Bu bağlamda, ülkemizin dördüncü büyük şehri olan Bursa'ya içme suyu sağlayan tesisin Ocak 2021 ile Haziran 2021 tarihleri arasında alınan 21 su numunesine ilişkin verileri, çeşitli ilişki analizi yöntemiyle incelenmiştir. Öncelikle, değerlendirilmek üzere olan 10 farklı (elektrik iletkenliği (EC), bakır (Cu), nikel (Ni), nitrat (?NO?_3^-), arsenik (As), demir (Fe), toplam çözünmüş maddeler (TDS), toplam alkalinite (TA), toplam sertlik (TH) ve çözünmüş oksijen (DO)) parametre arasındaki ilişkinin gücü ve yönü ilişki analizi, su kalite indeksi ve polinom eğri uydurma yöntemine tabi tutularak irdelenmiştir. Doğrusal korelasyon ilişki bulunmayan parametrelerin ilişkisi yorumlanmış ve son olarak ağırlıklı aritmetik su kalitesi indeksi (WAWQI) neticesinde tahsis edilen su deposundaki su kalitesinin içilebilirliğinin 'mükemmel' seviyede olduğu ve gereklilikleri karşıladığı tespit edilmiştir.
İçme Suyu Kalitesinin İstatistiksel Olarak Değerlendirmesi: Bursa Doburca Arıtma Tesisi Örneği
Keywords: Water Resources Engineering; Su Kaynakları Mühendisliği